2005
DOI: 10.4015/s1016237205000111
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Assessment of Montmorillonite as a Drug Carrier for Pharmaceutical Applications: Yeast and Rats Model

Abstract: Our previous study indicated that montmorillonite (MMT for short) was pharmaceutically feasible to be used as a carrier of an anticancer drug 5-FU. Emphasis of this study is thus placed on the toxicity of MMT to address whether it is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 2 publications
2
39
0
2
Order By: Relevance
“…Lee et al [62] showed that a prolonged 7-day exposure of human dermal fibroblasts to 0.001 % MMT did not lead to significant changes in cell viability. This echoes with the outcome of a study conducted earlier by Lee et al [63] whereby MMT was found to be biologically safe and nontoxic (Saccharomyces cerevisiae (24 h and *10 5 ppm) and Wistar rat (72 h and 142.9 mg/kg BW). As a result, the growth inhibitory effects as observed in the present study were likely the cocontribution from SA and methyl cellulose (MC-0), rather On the contrary, MC-1 and -5 exhibited growth promoting profiles at high concentrations of 100 and 1,000 lg/ ml.…”
Section: Cytotoxicity Profiles Of the Bionanocomposite Films And Theisupporting
confidence: 88%
“…Lee et al [62] showed that a prolonged 7-day exposure of human dermal fibroblasts to 0.001 % MMT did not lead to significant changes in cell viability. This echoes with the outcome of a study conducted earlier by Lee et al [63] whereby MMT was found to be biologically safe and nontoxic (Saccharomyces cerevisiae (24 h and *10 5 ppm) and Wistar rat (72 h and 142.9 mg/kg BW). As a result, the growth inhibitory effects as observed in the present study were likely the cocontribution from SA and methyl cellulose (MC-0), rather On the contrary, MC-1 and -5 exhibited growth promoting profiles at high concentrations of 100 and 1,000 lg/ ml.…”
Section: Cytotoxicity Profiles Of the Bionanocomposite Films And Theisupporting
confidence: 88%
“…SEM images of the crosssection of the explanted nanocomposite showed that fibroblasts were able to easily penetrate and attach to locations within the pore network and consequently produced pore walls with biocolonized surfaces. Although clay nanoparticles can be considered nontoxic 24 , surfactants used to improve the organophilic behavior of clays were reported to be toxic in some studies 26 . In this work, the synthesis of the nanocomposite was designed to enable the formation of chemical bonds between the alkylammonium (surfactant) and the polymer so as to restrict the free diffusion of this surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity related to nanoparticles derived from clay minerals is much less known. Some reports have demonstrated that these particles may be considered nontoxic 24,25 , since no histopathological changes could be observed in heart, liver, spleen, lung and kidney of rats after ingestion and intravenous injection of clay nanoparticles, as an indication that they could be eliminated through the kidney system. However, some chemical treatments used to improve the organophilic behavior of the clays may lead to toxicity 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior to indications of MMT as a good carrier for drug design, Lee et al [6] also examined acute effects of MMT using wistar rats as an in vivo animal model, clearly revealing the harmless nature of MMT. Evidence in biochemical analysis on mice administered with high doses of MMT also indicated that MMT is considered safe for practical use.…”
Section: Biomedical Engineering-applications Basis and Communicationsmentioning
confidence: 99%